Relationship between autoimmune thyroid antibodies and anti-nuclear antibodies in general patients - Ruan, Yi; Heng, Xian-pei; Yang, Liu-qing; He, Wei-dong; Li, Liang; Wang, Zhi-ta; Huang, Su-ping; Chen, Qi-wei; Han, Zhuang (Frontiers in Endocrinology, 2024)
Background: There is no doubt that both Hashimoto thyroiditis and Graves' disease are autoimmune thyroid diseases (AITDs), but the relationship between anti-nuclear antibody (ANA) and AITDs is poorly studied. The association between thyroid autoantibody levels and ANA positivity was evaluated to assess the role of ANA in AITDs.We conducted an analysis using data from 1,149,895 patients registered at our hospital and 53,021 patients registered in the National Health and Nutrition Examination Survey databases. We focused on patients with data for thyroid peroxidase antibody (TPOAb)/ANA, TPOAb/immunoglobulin G (IgG), thyroidstimulating hormone (TSH) receptor antibody (TRAb)/ANA, TRAb/IgG, TSH/ANA, or TSH/IgG.Results: ANA positivity rates were 12.03% and 19.85% in TPOAb/ANA and TSH/ANA patients, respectively. In TPOAb/IgG and TSH/IgG data, high IgG levels (≥15 g/L) were detected in 2.07% and 3.77% of patients, respectively. There were significant differences in ANA positivity rates and high IgG proportions among patients with different TPOAb and TSH levels. TPOAb level was correlated with ANA positivity rate and high IgG proportion, and TSH level was correlated with ANA positivity rate. Regression analysis showed positive correlations between TPOAb levels and ANA positivity risk or high IgG risk, TSH levels and high IgG risk, and elevated TSH and ANA positivity risk. Of patients with TRAb/ANA data, 35.99% were ANA-positive, and 13.93% had TRAb levels ≥1.75IU/L; 18.96% of patients with TRAb/IgG data had high IgG levels, and 16.51% had TRAb levels ≥1.75IU/L. ANA positivity rate and high IgG proportion were not significantly different among different TRAb levels. TRAb levels, ANA positivity risk and high IgG risk were not correlated. Conclusions: ANA positivity and high IgG are related to Hashimoto thyroiditis but not Graves' disease, which implies distinct pathophysiological mechanisms underlying the AITDs.